Evaluación del proceso de obtención de aceite esencial de semilla de mango a nivel laboratorio (2018)
The purpose of this work is to carry out the evaluation of the process of obtaining the essential oil of mango seed at the laboratory level, which was carried out under the direction of SENA's Tecnoparque. Was done in 4 stages, in the respective order, conditioning of the raw material, where the most optimal way to carry out the extraction process is obtained; the selection of the best extraction process; from the experimentally obtained data, the technical study is carried out and finally the financial study. With the evaluation made it is decided if it is viable to take it to an industrial level.